Platelet polyphosphates are proinflammatory and procoagulant mediators in vivo - Müller, Felicitas; Mutch, Nicola J; Schenk, Wolfdieter A; Smith, Stephanie A; Esterl, Lucie; Spronk, Henri M; Schmidbauer, Stefan; Gahl, William A; Morrissey, James H; Renné, Thomas (Cell, 2009)
Platelets play a central role in thrombosis, hemostasis, and inflammation. We show that activated platelets release inorganic polyphosphate (polyP), a polymer of 60-100 phosphate residues that directly bound to and activated the plasma protease factor XII. PolyP-driven factor XII activation triggered release of the inflammatory mediator bradykinin by plasma kallikrein-mediated kininogen processing. PolyP increased vascular permeability and induced fluid extravasation in skin microvessels of mice. Mice deficient in factor XII or bradykinin receptors were resistant to polyP-induced leakage. PolyP initiated clotting of plasma via the contact pathway. Ablation of intrinsic coagulation pathway proteases factor XII and factor XI protected mice from polyP-triggered lethal pulmonary embolism. Targeting polyP with phosphatases interfered with procoagulant activity of activated platelets and blocked platelet-induced thrombosis in mice. Addition of polyP restored defective plasma clotting of Hermansky-Pudlak Syndrome patients, who lack platelet polyP. The data identify polyP as a new class of mediator having fundamental roles in platelet-driven proinflammatory and procoagulant disorders.